Mussel-inspired adhesive antioxidant antibacterial hemostatic composite hydrogel wound dressing via photo-polymerization for infected skin wound healing - Yutong Yang (KeAi Communications Co., Ltd., 2022)
With the increasing prevalence of drug-resistant bacterial infections and the slow healing of chronically infected wounds, the development of new antibacterial and accelerated wound healing dressings has become a serious challenge. In order to solve this problem, we developed photo-crosslinked multifunctional antibacterial adhesive anti-oxidant hemostatic hydrogel dressings based on polyethylene glycol monomethyl ether modified glycidyl methacrylate functionalized chitosan (CSG-PEG), methacrylamide dopamine (DMA) and zinc ion for disinfection of drug-resistant bacteria and promoting wound healing. The mechanical properties, rheological properties and morphology of hydrogels were characterized, and the biocompatibility of these hydrogels was studied through cell compatibility and blood compatibility tests. These hydrogels were tested for the in vitro blood-clotting ability of whole blood and showed good hemostatic ability in the mouse liver hemorrhage model and the mouse-tail amputation model. In addition, it has been confirmed that the multifunctional hydrogels have good inherent antibacterial properties against Methicillin-resistant Staphylococcus aureus (MRSA). In the full-thickness skin defect model infected with MRSA, the wound closure ratio, thickness of granulation tissue, number of collagen deposition, regeneration of blood vessels and hair follicles were measured. The inflammation-related cytokines (CD68) and angiogenesis-related cytokines (CD31) expressed during skin regeneration were studied. All results indicate that these multifunctional antibacterial adhesive hemostatic hydrogels have better healing effects than commercially available Tegaderm™ Film, revealing that they have become promising alternative in the healing of infected wounds.